2000
DOI: 10.1056/nejm200003163421103
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept in Children with Polyarticular Juvenile Rheumatoid Arthritis

Abstract: Treatment with etanercept leads to significant improvement in patients with active polyarticular juvenile rheumatoid arthritis. Etanercept is well tolerated by pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
590
4
91

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,098 publications
(707 citation statements)
references
References 31 publications
22
590
4
91
Order By: Relevance
“…These findings, despite the difference in the study design, are similar to those observed during the openlabel phase of a trial assessing the use of etanercept in JRA (8), and demonstrate the value of infliximab in maintaining efficacy for up to 1 year. Of note, 78 of the 122 children enrolled in the study (63.9%) subsequently entered a 3-year open-label extension.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These findings, despite the difference in the study design, are similar to those observed during the openlabel phase of a trial assessing the use of etanercept in JRA (8), and demonstrate the value of infliximab in maintaining efficacy for up to 1 year. Of note, 78 of the 122 children enrolled in the study (63.9%) subsequently entered a 3-year open-label extension.…”
Section: Discussionsupporting
confidence: 74%
“…The ACR Pedi 30 criteria have been validated, and their reliability in discriminating between active agent and placebo has been established in studies of NSAIDs (24,25), MTX (6), etanercept (8), and more recently, other biologic agents (26,27). We believe the lack of statistical significance between treatment groups in the present study resulted from the combination of a small sample size (60 patients per treatment group) and a higher-than-anticipated rate of response (49.2%) in the placebo group (28), which was likely due to a greater placebo effect associated with agents administered by infusion and a placebo treatment phase that was too brief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to put our results in perspective, in 2 recent clinical trials, 44% and 33% of patients with a severe polyarticular disease course who had failed treatment with methotrexate achieved an ACR Pedi 70 criteria response after 7 and 12 months, respectively, with etanercept, and in another trial, 52% reached this response after 1 year of infliximab treatment (21,22,28). The ACR Pedi 70 criteria response rate 6 months after starting methotrexate was 26% in a study of patients with polyarthritis, systemic arthritis, and extended oligoarthritis (17).…”
Section: Discussionmentioning
confidence: 92%
“…Subsequently, a higher dosage of MTX, up to 30 mg/m 2 / week, has been suggested as a therapeutic option for patients whose condition remains resistant to the standard dosage, but no randomized trial has ever confirmed this hypothesis (5). Although anti-tumor necrosis factor (anti-TNF) agents (6) have become available in recent years for the treatment of MTX-resistant patients, these medications are expensive and not available to all patients. Therefore, the definition of the optimal dosage of MTX in terms of efficacy and safety remains central to disease management.…”
mentioning
confidence: 99%